2015
DOI: 10.1371/journal.pone.0130631
|View full text |Cite|
|
Sign up to set email alerts
|

Is Placental Mitochondrial Function a Regulator that Matches Fetal and Placental Growth to Maternal Nutrient Intake in the Mouse?

Abstract: BackgroundEffective fetal growth requires adequate maternal nutrition coupled to active transport of nutrients across the placenta, which, in turn requires ATP. Epidemiological and experimental evidence has shown that impaired maternal nutrition in utero results in an adverse postnatal phenotype for the offspring. Placental mitochondrial function might link maternal food intake to fetal growth since impaired placental ATP production, in response to poor maternal nutrition, could be a pathway linking maternal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Indeed, in a study of placental tissues from IUGR and preeclamptic pregnancies, mitochondrial protein expression and function (increased respiratory chain complex activity) were found to be increased in different areas of IUGR placentas (245) while mitochondrial DNA content was increased in cord blood from monochorionic twins with IUGR (65), providing a theoretical capacity for increased mitochondrial production of ROS in the placenta. Interestingly, in a study by Chiaratti et al (74), placental mitochondrial DNA content was found to be in-versely correlated to mouse fetal weight in a model of maternal low protein. Skeletal mitochondrial function was also shown to be increased in the mouse offspring of a maternal low-protein-diet pregnancy (186), an effect that was thought to protect offspring against high-fat diet-induced obesity but may also result in increased ROS production.…”
Section: Oxidative Stressmentioning
confidence: 96%
“…Indeed, in a study of placental tissues from IUGR and preeclamptic pregnancies, mitochondrial protein expression and function (increased respiratory chain complex activity) were found to be increased in different areas of IUGR placentas (245) while mitochondrial DNA content was increased in cord blood from monochorionic twins with IUGR (65), providing a theoretical capacity for increased mitochondrial production of ROS in the placenta. Interestingly, in a study by Chiaratti et al (74), placental mitochondrial DNA content was found to be in-versely correlated to mouse fetal weight in a model of maternal low protein. Skeletal mitochondrial function was also shown to be increased in the mouse offspring of a maternal low-protein-diet pregnancy (186), an effect that was thought to protect offspring against high-fat diet-induced obesity but may also result in increased ROS production.…”
Section: Oxidative Stressmentioning
confidence: 96%
“…In the human and rodent placenta, both nutritional and hypoxic stresses alter mitochondrial function. More specifically, there are changes in mitochondrial biogenesis, morphology, apoptosis and abundance of electron transport complexes and uncoupling proteins during common pregnancy stresses including maternal diabetes, obesity, pre‐eclampsia, calorie restriction, protein deprivation and high‐altitude hypoxia (Belkacemi, Desai, Nelson Michael, & Ross Michael, ; Chiaratti et al., ; Colleoni et al., ; Hastie & Lappas, ; Hercules, Esquisatto, Moraes, Amaral, & Catisti, ; Mando et al., ; Mayeur et al., ). Increased abundance of uncoupling protein‐2 has also been observed in the ovine placenta at mid‐gestation and late gestation of ewes undernourished during early pregnancy (Gnanalingham et al., ).…”
Section: Oxygenmentioning
confidence: 99%
“…). Certainly in humans and mice, nutritional and hypoxic stimuli alter placental ATP content (Chiaratti et al., ; Tissot van Patot et al., ). Consequently, even though placental O 2 consumption is maintained during many stressful conditions (Fig.…”
Section: Oxygenmentioning
confidence: 99%
“…Effective fetal growth is dependent on the transport of nutrients from the placenta to the fetus, which requires ATP, insulin, and several growth factors, including IGF-1 . Changes in mitochondrial morphology detected with high throughput imaging suggest that placental mitochondrial function is a regulator of fetal and placental growth [75]. However, our results suggest that mitochondrial function may be linked to adverse birth outcomes via earlier gestational age rather than via intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 89%